Analisis Kualitas dan Efektivitas Filter Air dari Limbah Kelapa pada Air Tanah - Firda Ainun Nisah; Halida Ainun Nazwa; Riki Renaldi (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2023)
On Karawang utara has problems with groundwater and coconut waste. Groundwater in the area is crusty and yellowish in color. Coconut waste comes from sellers who only take coconut meat and water, leaving coconut husks and shells. To overcome these problems, conducted groundwater quality test and made water filters from coconut waste. The parameters tested were pH, TDS, manganese, and iron. According to Minister of Health Regulation Number 32 of 2017 and Regulation of Minister of Health Number 492 of 2010, groundwater quality testing showed that groundwater in all areas of Karawang utara can be used for sanitation purposes, but only Pedes and Tirta Jaya regions can be used as raw material for drinking water The design of the water filter from coconut waste is designed to solve this problem.. The results of groundwater testing after the filtration process have values below the threshold of PerMenKes Number 492 of 2010 which indicates that groundwater after the filtration process can be used as raw material for drinking water. The effectiveness of water filters from coconut waste reduces TDS 32.05%, manganese 82.01%, and iron 83.33%. The design of a water filter that has been made is proven to be able to solve groundwater problems and coconut waste problems in Karawang utara.